Analysis of Seven Drug Related Impurities in Six Samples of Metronidazole API by High Performance Liquid Chromatography - Derouicha Matmour; Nadjib Hamoum; Khalil Fateh Eddine Hassam; Yassine Merad; Nassima Hamdi Ziani (Journal of Trace Elements and Minerals, 2023)
Introduction: The main objective of this work was to analysis seven drug related impurities by High Performance Liquid Chromatography (HPLC) in six samples of Metronidazole API, collected from six pharmaceutical industries installed in Algeria. Materials and methods: For the organic related-impurities analysis, a liquid chromatography apparatus HPLC-UV device equipped with an automatic injector and UV/Vis detector and a column (C18), deactivated for the bases, post-grafted (5 µm) and dimensions (w: 0.25 m, Ø: 4.6 mm) were used. Each sample of Metronidazole API was processed according to the related substances procedures of the European Pharmacopoeia (Eur pH), 8th edition. Results: The HPLC related-impurities analysis showed that the M1, M2, M3, M4 and M6 samples had an individual content of impurity A or any other unspecified impurity within the required standards and a total of all impurities present meeting the standard. M5 sample had a high content of unspecified impurity 0.170% compared to the general acceptance criterion, and a total of impurities 0.187% meeting the standard. This can be explained either by the degradation of the sample which may be due to poor storage conditions or the batch from which this sample comes was not well purified during the synthesis route. Conclusion: Seven drug related impurities were analyzed in six samples of Metronidazole API by HPLC. The impurity A and the unspecified impurities were precisely determined in the different samples of Metronidazole analyzed. All samples had an individual content and a total of all impurities present meeting the standard except M5 sample had a high content of unspecified impurity 0.170% and a total of impurities 0.187% meeting the standard.